MODIFIKASI LAGU “RAYUAN PEREMPUAN GILA” DENGAN FORMAT REMIX PADA TIKTOK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA TAHUN 2017 TENTANG PEMILIHAN UMUM: The Modification of “Rayuan Perempuan Gila” Song Into Remix Format on TikTok Platform Based on CopyrightAct Number 28 of 2014 - Zahran, Dhebilla Kamiliya; Desmayanti, Rakhmita (AMICUS CURIAE, 2024)
Songs are objects protected by copyright, with the development of technology there can be copyright violations against songs, namely in the form of song modifications without the author's permission which have detrimental impacts. This research discusses violations of copyright law related to the modification of the song "Rayuan Perempuan Gila" on TikTok based on Law Number 28 of 2014 concerning Copyright and what actions can be taken regarding copyright violations. This research uses a normative research method with descriptive research characteristics, the data used is secondary data as the main data, analysis uses qualitative methods and conclusions are drawn using deductive methods. Based on the research results, the song "Rayuan Perempuan Gila" which has been modified with a remix format and uploaded on TikTok is included in a violation of copyright law in terms of moral and economic rights because it creates a loss for the creator and/or copyright holder as well as actions that can be taken by creators and/or copyright holders regarding copyright violations, namely by submitting a complaint to the Directorate General of Intellectual Property Rights (DJKI) in collaboration with the Ministry of Communication and Information (Kemenkominfo) to carry out executions of copyright violations. Therefore, the author recommends that the perpetrator of the modification should ask permission from the creator to modify the song and upload it to TikTok.